Layered double hydroxide, catalyst for water electrolysis unit, water electrolysis unit, water electrolysis device, and method for producing layered double hydroxide
By synthesizing layered complex hydroxides (LDHs) containing transition metals and chelating agents, the problem of large overvoltage of the anode reaction in water electrolysis is solved, and catalytic activity and hydrogen manufacturing efficiency are significantly improved.
Patent Information
- Application Number
- CN202080009243.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-10
- Filing Date
- 2020-04-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-04-28
AI Technical Summary
In water electrolysis, the overvoltage of the anode reaction is large, which affects the efficiency of hydrogen manufacturing. The activity of existing catalyst materials is insufficient, making it difficult to meet the needs of efficient hydrogen manufacturing.
By synthesizing a layered complex hydroxide (LDH) containing two or more transition metals and a chelating agent, the average particle size is 100 nm or less, and is used as a catalyst for the water electrolytic anode reaction.
The catalytic activity of the water electrolytic anode reaction is significantly improved, the specific surface area of the catalyst is increased, and the hydrogen manufacturing efficiency is improved.
Smart Images

Figure CN113302341B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a layered double hydroxide, a catalyst for a water electrolysis cell, a water electrolysis cell, a water electrolysis device, and a method for producing the layered double hydroxide. Background Art
[0002] Hydrogen production by water electrolysis (hereinafter referred to as water electrolysis) is an effective technology for converting surplus electricity from renewable energy sources with large output fluctuations, such as sunlight and wind power, into hydrogen for storage and utilization.
[0003] Here, when water electrolysis is used to achieve efficient hydrogen production, the magnitude of the overvoltage of the oxygen production reaction at the anode in water electrolysis (hereinafter sometimes referred to as the anode reaction of water electrolysis) is considered to be a problem. Therefore, the development of highly active catalyst materials for the anode reaction of water electrolysis is underway.
[0004] Specifically, layered double hydroxide (hereinafter sometimes referred to as LDH (Layered Double Hydroxide)) has attracted attention as a promising catalyst material for the anode reaction of water electrolysis because it can increase the specific surface area and has various combinations of metal ions, and various reports have been made.
[0005] For example, it is generally known that LDH containing transition metals as constituent elements can be synthesized by making an aqueous solution containing two or more transition metals alkaline, and that LDH functions as a catalyst for an anode reaction in water electrolysis.
[0006] Furthermore, Non-Patent Document 1 reports that LDH nanoparticles having an average particle size of 10 nm or less can be formed by ultrasonic pulverization, and that the use of the LDH nanoparticles as a catalyst material improves the catalytic activity of the anode reaction of water electrolysis.
[0007] Prior Art Literature
[0008] Non-patent literature
[0009] Non-patent document 1: Yufei Zhao et al., "Sub-3nm Ultrafine Monolayer LayeredDouble Hydroxide Nanosheets for Electrochemical Water Oxidation", Advanced Energy Materials Vol.8, 1703585 (2018)
[0010] Non-patent document 2: Yasuaki Tokudome et al., "Layered Double Hydroxide Nanoclusters: Aqueous, Concentrated, Stable, and Catalytically Active Colloidstoward Green Chemistry", American Chemical Society Nano 2016, 10, 5550-5559 Summary of the invention
[0011] An object of the present disclosure is to provide, as one example, an LDH capable of exhibiting a higher catalytic activity than before in an anode reaction of water electrolysis.
[0012] In order to solve the above-mentioned problems, LDH according to one aspect of the present disclosure includes two or more transition metals and a chelating agent, and has an average particle size of 100 nm or less.
[0013] The LDH according to one embodiment of the present disclosure can achieve an effect of exhibiting higher catalytic activity than ever before in the anode reaction of water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a diagram showing an example of a method for synthesizing LDH containing two general transition metals by a precipitation method.
[0015] Figure 2 This is a diagram showing an example of a synthesis process of Ni—Al-based LDH nanoparticles disclosed in a conventional example.
[0016] Figure 3 This is a diagram showing an example of the synthesis mechanism of the LDH nanoparticles disclosed in the present invention.
[0017] Figure 4 This is a diagram showing an example of the crystal structure of LDH.
[0018] Figure 5 This is a diagram showing an example of LDH nanoparticles (primary particles) according to the first embodiment.
[0019] Figure 6 This is a diagram showing an example of a water electrolysis unit according to the fifth embodiment.
[0020] Figure 7 This is a diagram showing an example of a water electrolysis device according to a sixth embodiment.
[0021] Figure 8 This is a diagram showing an example of an XRD spectrum of a sample obtained in Example 1.
[0022] Fig. 9 This is a diagram showing an example of the particle size distribution of the sample obtained in Example 1. DETAILED DESCRIPTION
[0023] As a result of intensive studies to improve the catalytic activity of LDH, it was found that the catalytic activity is improved by including a chelating agent in LDH having two or more transition metal components.
[0024] That is, the LDH according to the first aspect of the present disclosure contains two or more transition metals and a chelating agent, and has an average particle size of 100 nm or less.
[0025] According to this configuration, the LDH of the present embodiment can exhibit higher catalytic activity than ever before in the anode reaction of water electrolysis.
[0026] For example, the LDH of the present embodiment can exhibit higher catalytic activity in the anode reaction of water electrolysis by containing a chelating agent, compared with the case where no chelating agent is contained (for example, Non-Patent Document 1).
[0027] In addition, the LDH of the present embodiment can appropriately improve the catalytic activity by setting the average particle diameter to 100 nm or less, compared with the case where the average particle diameter is larger than 100 nm.
[0028] The LDH of the second aspect of the present disclosure is the LDH of the first aspect, wherein the average particle size of the LDH may be 50 nm or less.
[0029] According to this configuration, the average particle size of LDH becomes smaller, so the specific surface area (catalyst surface area per unit mass) of LDH increases, and the activity increases.
[0030] The LDH of the third aspect of the present disclosure is the LDH of the first aspect or the second aspect, wherein the average particle size of the LDH may be 10 nm or less.
[0031] According to this configuration, the average particle size of LDH becomes smaller, so the specific surface area (catalyst surface area per unit mass) of LDH increases, and the activity increases.
[0032] The fourth aspect of the LDH disclosed herein is the LDH of any one of the first to third aspects, wherein the two or more transition metals are two or more metals selected from V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru.
[0033] The LDH of a fifth aspect of the present disclosure is the LDH of any one of the first to fourth aspects, wherein the two or more transition metals may include either Ni or Fe.
[0034] It is known that among transition metals, nickel (Ni) and iron (Fe) have particularly high catalytic activity for the anode reaction of water electrolysis. Therefore, the LDH of this mode can show high catalytic activity in the anode reaction of water electrolysis by containing either Ni and Fe, compared with the case of selecting other transition metals. In addition, Ni and Fe are abundant elements, so the LDH of this mode can reduce material costs by containing either Ni and Fe, compared with the case of selecting other transition metals.
[0035] The sixth embodiment of the LDH disclosed herein is based on the LDH of any one of the first to fifth embodiments, wherein the two or more transition metals may be composed of Ni and Fe, and the ratio of the amount of Fe to the total amount of Ni and Fe may be greater than 0.25 and less than 0.5.
[0036] According to this configuration, the LDH of this embodiment contains Ni and Fe so that the ratio is within the range of 0.25 to 0.5, and can exhibit high catalytic activity in the anode reaction of water electrolysis compared with a case where the ratio is outside the above range.
[0037] The LDH of the seventh aspect of the present disclosure is the LDH of any one of the first to sixth aspects, wherein the chelating agent may be a chelating agent containing any one of acetylacetone and a citrate such as trisodium citrate.
[0038] The 8th embodiment of the LDH disclosed herein is based on the LDH of any one of the 1st to 7th embodiments, wherein the chelating agent may be acetylacetone; and the absorbance at 300nm when the optical path length is 10mm obtained by ultraviolet visible absorbance measurement (UV-vis) may be greater than 0.75 and less than 1.0.
[0039] When the coordination amount of the chelating agent is such that the absorbance at 300 nm obtained by UV-vis absorption measurement is 0.75 or more and 1.0 or less, the aggregation of LDH can be inhibited. In addition, when LDH is used as a catalyst material, the inhibitory effect of the chelating agent can also be obtained.
[0040] The LDH of the ninth aspect of the present disclosure is the LDH of any one of the first to eighth aspects, wherein the average particle size obtained by small angle X-ray scattering (SAXS) may be 100 nm or less.
[0041] According to this configuration, the LDH of the present embodiment can appropriately improve catalytic activity compared to a case where the average particle diameter is larger than 100 nm by making the average particle diameter obtained by small-angle X-ray scattering (SAXS) 100 nm or less.
[0042] The LDH of the tenth aspect of the present disclosure is based on the LDH of any one of the first aspect to the ninth aspect, and can be replaced by [M 2+ 1-x M 3+ x (OH)2][yA n- ·mH2O] composition formula, and the chelating agent is coordinated with the above two or more transition metals. In this composition formula, M 2+ is a divalent transition metal, M 3+ A is a trivalent transition metal. n- is the interlayer anion, m is an appropriate rational number, n is an integer, x is a rational number not exceeding 1, and y is a number equivalent to the amount required for charge balance.
[0043] The catalyst for a water electrolysis unit according to the eleventh aspect of the present disclosure may include the LDH according to any one of the first to tenth aspects.
[0044] According to this configuration, the catalyst for a water electrolysis unit of the present embodiment can exhibit a catalytic activity higher than before in the anode reaction of water electrolysis.
[0045] The water electrolysis unit according to the twelfth aspect of the present disclosure may include a positive electrode containing the catalyst according to the eleventh aspect, a negative electrode, and an electrolyte.
[0046] According to this configuration, the water electrolysis unit of this embodiment can show a higher catalytic activity than before in the anode reaction of water electrolysis. Even in the state of the water electrolysis unit, the chelating agent remains in the catalyst to suppress the aggregation of the catalyst, and the energy conversion efficiency of water electrolysis is improved due to the increase in catalytic active points.
[0047] The water electrolysis unit according to the 13th aspect of the present disclosure may include a positive electrode, a negative electrode containing the catalyst according to the 11th aspect, and an electrolyte.
[0048] The water electrolysis device according to the fourteenth aspect of the present disclosure may include the water electrolysis unit according to the twelfth aspect or the thirteenth aspect, and a voltage applicator for applying a voltage to the positive electrode and the negative electrode.
[0049] According to this configuration, the water electrolysis device of this embodiment can show higher catalytic activity than before in the anode reaction of water electrolysis. Even in the state of water electrolysis unit, the chelating agent remains in the catalyst to suppress the aggregation of the catalyst, and the energy conversion efficiency of water electrolysis is improved due to the increase of catalytic active points.
[0050] The method for producing LDH according to the fifteenth aspect of the present disclosure comprises the steps of preparing an aqueous solution containing two or more transition metal ions and a chelating agent and making the aqueous solution alkaline.
[0051] As described above, the method for producing LDH of the present embodiment can obtain LDH that exhibits higher catalytic activity than conventional methods in the anode reaction of water electrolysis.
[0052] For example, the method for producing LDH of the present embodiment can obtain LDH that exhibits high catalytic activity in the anode reaction of water electrolysis by including a chelating agent, compared with the case where no chelating agent is included.
[0053] The method for producing LDH according to the sixteenth aspect of the present disclosure may further include the step of increasing the pH of the alkaline aqueous solution in addition to the method for producing LDH according to the fifteenth aspect.
[0054] The method for producing LDH according to the seventeenth aspect of the present disclosure is the method for producing LDH according to the fifteenth aspect, wherein the aqueous solution can be made alkaline at room temperature.
[0055] The method for producing LDH according to the eighteenth aspect of the present disclosure is the method for producing LDH according to the sixteenth aspect, wherein the pH of the alkaline aqueous solution can be increased at room temperature.
[0056] As described above, the method for producing LDH of the present embodiment can suppress the chelating agent coordinated to the transition metal ion from being decomposed by heat by performing the synthesis process of LDH at room temperature.
[0057] In the 19th method for producing LDH of the present disclosure, based on the method for producing LDH of any one of the 15th to 18th methods, the two or more transition metals may be two or more metals selected from V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru.
[0058] The method for producing LDH according to a 20th aspect of the present disclosure is the method for producing LDH according to any one of the 15th to 19th aspects, wherein the two or more transition metals may include either Ni or Fe.
[0059] It is known that among transition metals, nickel (Ni) and iron (Fe) have particularly high catalytic activity for the anode reaction of water electrolysis. Therefore, the method for producing LDH of the present embodiment, by containing any one of Ni and Fe, can obtain LDH showing high catalytic activity in the anode reaction of water electrolysis compared with the case of selecting other transition metals. In addition, since Ni and Fe are abundantly present elements, the method for producing LDH of the present embodiment, by containing any one of Ni and Fe, can reduce material cost compared with the case of selecting other transition metals.
[0060] Regarding the method for producing the LDH material disclosed in the present invention, the following studies were conducted with the purpose of nanoparticle formation of LDH.
[0061] First, refer to Figure 1 , while explaining a general method for synthesizing LDH containing two transition metals by a precipitation method.
[0062] like Figure 1 As shown, by making an aqueous solution containing two transition metals TM1 and TM2 alkaline, LDH primary particles P1 including these transition metals TM1 and TM2 as constituent elements are synthesized. Such a synthesis method is generally well known, and therefore a detailed description thereof is omitted.
[0063] However, in this general synthetic method, e.g. Figure 1 As shown, LDH primary particles P1 (particle size of 10 nm or less) tend to aggregate to form LDH secondary particles P2 (particle size of several hundred nm) in order to reduce their surface energy. As a result, the specific surface area of LDH secondary particles P2 is reduced compared to LDH primary particles P1, resulting in a problem of reduced catalytic activity.
[0064] Therefore, in "ACSNano 10, 5550 (2016)" (hereinafter referred to as the previous example), a method for synthesizing Ni-Al-based LDH nanoparticles was proposed: in an aqueous solution containing amphoteric element aluminum (Al) and transition element nickel (Ni), acetylacetone (ACAC: Acetyl Acetone) was added as a chelating agent, and the aqueous solution was made alkaline. Thus, the previous example disclosed that by controlling the crystal growth and aggregation of LDH primary particles, Ni-Al-based LDH nanoparticles with a particle size of about 7.8nm can be synthesized.
[0065] Figure 2 This is a diagram showing an example of a synthesis process of Ni—Al-based LDH nanoparticles disclosed in a conventional example.
[0066] like Figure 2 As shown, when Ni ions (Ni 2+ ), Al ions (Al 3+ ) and the pH value of the aqueous solution of the chelating agent increases, Al is first precipitated as hydroxide.
[0067] In this process, the chelating agent is partially coordinated to the Al hydroxide (Al(OH)x).
[0068] Then, when the pH value of the aqueous solution is further increased, Ni begins to precipitate as a hydroxide, and the amphoteric element Al redissolves from the Al hydroxide as an ion. At this time, the chelating agent has two functions. First, the chelating agent has the function of promoting the redissolution of Al from the Al hydroxide by reducing the size of the Al hydroxide. Second, the chelating agent has the function of coordinating with both the redissolved Al ions and the Ni ions in the aqueous solution, thereby acting as a capping agent to control the crystal growth of the LDH nanoparticles. Thus, the chelating agent can inhibit the agglomeration of the LDH nanoparticles.
[0069] In this way, it has been reported in the prior art that Ni—Al-based LDH nanoparticles can be synthesized.
[0070] However, the present inventors have studied the synthesis of LDH nanoparticles using transition metals as constituent elements with the goal of increasing the efficiency of the anode reaction of water electrolysis, but in the synthesis of such LDH, the same synthesis mechanism as in the previous examples is difficult to function. The reason is that transition metals that show high activity in the anode reaction of water electrolysis are generally not amphoteric elements, so it is difficult for the transition metal to dissolve again from the transition metal hydroxide.
[0071] Therefore, the present inventors conducted intensive studies and found that setting the solubility of the complex of the transition metal and the chelating agent in water and the concentration of the chelating agent added in the aqueous solution to appropriate amounts is suitable for the synthesis of LDH nanoparticles.
[0072] Figure 3 is a diagram showing an example of the synthesis mechanism of the LDH nanoparticles disclosed in the present invention. Figure 3 Schematic diagram showing the case where two transition metals TM1 and TM2 are contained in an aqueous solution.
[0073] like Figure 3 As shown in FIG. 1 , when the pH value of an aqueous solution containing a transition metal TM1 (ion), a transition metal TM2 (ion) and a chelating agent is increased, first the transition metal TM2 is converted into a hydroxide “TM2(OH) x "precipitation.
[0074] Here, in order to synthesize LDH nanoparticles, it is necessary to synthesize LDH by reacting transition metal ions in an aqueous solution with each other, rather than reacting the hydroxide of the transition metal TM2 with the transition metal TM1 in the solution.
[0075] Therefore, the present inventors speculate that when the solubility of the complex of the transition metal and the chelating agent in water is above an appropriate amount, even the transition metal TM2 which is difficult to redissolve from the hydroxide can be dissolved. Figure 3As shown, the transition metal TM2 can be captured by the chelating agent to redissolve the transition metal TM2. That is, the present inventors speculate that when the solubility of the complex of the transition metal and the chelating agent in water is above an appropriate amount, the amount of transition metal ions in the aqueous solution required for the synthesis of LDH nanoparticles can be appropriately ensured.
[0076] Specifically, it is estimated that when the solubility of the complex of the transition metal and the chelating agent in water is 2 g / L or more, the amount of two or more transition metal ions in the aqueous solution required for the synthesis of LDH nanoparticles can be appropriately ensured.
[0077] That is, in the method for producing LDH according to the 21st aspect of the present disclosure, in addition to the method for producing LDH according to any one of the 15th to 20th aspects, the solubility of the complex of the transition metal and the chelating agent in water may be 2 g / L or more.
[0078] As described above, the method for producing LDH in this embodiment can appropriately ensure the concentration of transition metal ions in the aqueous solution required for LDH synthesis by reaction between transition metal ions in the aqueous solution, as compared with the case where the solubility of the complex of transition metal and chelating agent in water is greater than 2 g / L.
[0079] The method for producing LDH according to the 22nd aspect of the present disclosure is the method for producing LDH according to any one of the 15th to 21st aspects, wherein the chelating agent may be a chelating agent containing either acetylacetone or citrate.
[0080] It is generally known that the solubility of a complex of a transition metal and acetylacetone and the solubility of a complex of a transition metal and citrate are 2 g / L or more. Therefore, as the chelating agent in the method for producing LDH of the present embodiment, either acetylacetone or citrate can be used.
[0081] In addition, the present inventors speculate that when the concentration of the chelating agent added in the aqueous solution is below the appropriate amount, the transition metal TM1 partially coordinated by the chelating agent and the transition metal TM2 partially coordinated by the chelating agent are likely to react. In other words, when the concentration of the chelating agent added in the aqueous solution is greater than the appropriate amount, there is a possibility that the following problem will occur: the transition metal TM1 and the transition metal TM2 are coordinated with the chelating agent to the extent that the reaction between the transition metals TM1 and TM2 is inhibited, but it is believed that such a problem can be alleviated by setting the concentration of the chelating agent added in the aqueous solution to below the appropriate amount.
[0082] That is, the method for producing LDH according to the 23rd aspect of the present disclosure is the method for producing LDH according to any one of the 15th to 22nd aspects, wherein the chelating agent may be added at a concentration of 1 / 2.5 or less of the transition metal ion concentration.
[0083] As described above, the method for producing LDH of the present embodiment, by adding a chelating agent at a concentration of 1 / 2.5 or less of the transition metal ion concentration, can obtain LDH that exhibits high catalytic activity in the anode reaction of water electrolysis, compared to the case where the chelating agent is added at a concentration greater than 1 / 2.5 of the transition metal ion concentration.
[0084] Hereinafter, the embodiments of the present invention will be described with reference to the attached drawings. Figure 1 Specific description is given while. Furthermore, the embodiments described below all represent general or specific examples. Therefore, the numerical values, shapes, materials, constituent elements, configuration positions of constituent elements, and connection forms shown in the following embodiments are examples and are not intended to limit the present disclosure. In addition, among the constituent elements of the following embodiments, constituent elements that are not recorded in the independent claims representing the highest concept are described as arbitrary constituent elements. In addition, in the drawings, parts marked with the same mark are sometimes omitted. In addition, the drawings are diagrams that schematically show each constituent element for easy understanding, and are sometimes not accurate representations of shapes and size ratios.
[0085] In the production method, the order of the steps may be changed as necessary, and a known step may be added.
[0086] (First embodiment)
[0087] [Composition of LDH]
[0088] <Crystal structure of LDH>
[0089] The LDH of this embodiment includes two or more transition metals and a chelating agent. Furthermore, in the LDH of this embodiment, the two or more transition metals may be two or more metals selected from V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru. The chelating agent is a ligand having multiple coordination teeth, i.e., a multidentate ligand. As an example of the chelating agent, acetylacetone can be cited.
[0090] Here, Figure 4 This is a diagram showing an example of the crystal structure of LDH.
[0091] Such LDH is used [M 2+ 1-x M 3+ x (OH)2][yA n-That is, in the LDH of the present embodiment, the chelating agent is coordinated with the transition metal represented by the above composition formula.
[0092] Furthermore, in the above composition formula, M 2+ is a divalent transition metal, M 3+ A is a trivalent transition metal. n- is the interlayer anion, m is an appropriate rational number, n is an integer, x is a rational number not exceeding 1, and y is a number equivalent to the amount required for charge balance.
[0093] like Figure 4 As shown, in LDH, OH - Ions are located in M 2+ and M 3+ The vertices of the octahedron centered at the center, the metal hydroxide (composition formula: [M 2+ 1-x M 3+ x (OH)2]) has a layered (sheet-like) structure in which octahedrons have common edges and extend two-dimensionally. In addition, anions and water molecules are located between the two layers of the metal hydroxide. The layer of the metal hydroxide acts as a main layer 10, and the anions and water molecules are inserted as guest layers 20. That is, as a whole, LDH has a structure in which the main layer 10 of the metal hydroxide and the guest layer 20 of the anions and water molecules are alternately stacked.
[0094] <LDH Nanoparticles>
[0095] The average particle size of the LDH nanoparticles of the present embodiment is less than 100nm. Specifically, the LDH of the present embodiment has a primary particle containing one or more tiny single crystal regions, and a structure in which these primary particles are assembled and constitute secondary particles. The average particle size is calculated, for example, based on the particle size distribution (a particle size distribution reflecting the particle size of primary particles and secondary particles) obtained using a small-angle X-ray scattering method (SAXS). The average particle size can be less than 100nm. In addition, the average particle size of the LDH nanoparticles of the present embodiment calculated by the above method can be less than 50nm, or less than 10nm. Furthermore, the details of the "average particle size" are described in the examples.
[0096] Figure 5 This is a diagram showing an example of LDH nanoparticles (primary particles) according to the first embodiment.
[0097] like Figure 5 As shown, the LDH nanoparticle 50 of the present embodiment is a plate-shaped particle.
[0098] Here, when the LDH nanoparticle 50 of the present embodiment is used as a catalyst material for the anode reaction of water electrolysis, the active points are transition metal cations and / or oxygen anions bridging transition metal cations, and there are active points located at the outermost layer of the plate-shaped LDH nanoparticle 50 and active points located at the edge of the plate-shaped LDH nanoparticle 50.
[0099] Generally, specific activity (the current value derived from the catalytic reaction per unit amount of catalyst loaded) is used as an evaluation index of the catalytic activity of an electrode. By reducing the particle size, the specific surface area (catalyst surface area per unit mass) of LDH increases, thereby increasing the activity.
[0100] As described above, the LDH of the present embodiment can exhibit higher catalytic activity than ever before in the anode reaction of water electrolysis.
[0101] For example, the LDH of the present embodiment, by including a chelating agent, can show high catalytic activity in the anode reaction of water electrolysis compared to the case where the chelating agent is not included (for example, non-patent document 1). Specifically, it is known that when the LDH to which a chelating agent is added is used as a catalyst for a water electrolysis unit, the oxygen production current of the anode reaction of water electrolysis increases compared to the case where the LDH to which a chelating agent is not added. The details are described in the evaluation of the embodiment.
[0102] In addition, the LDH of the present embodiment can appropriately improve the catalytic activity by making the average particle size less than 100 nm, compared with the case where the average particle size is greater than 100 nm. For example, the LDH of the present embodiment can appropriately improve the catalytic activity by making the average particle size obtained by small-angle X-ray scattering (SAXS) less than 100 nm, compared with the case where the average particle size is greater than 100 nm.
[0103] [Method for producing LDH]
[0104] The method for producing LDH of the present embodiment comprises a step of preparing an aqueous solution and a step of making the aqueous solution alkaline, wherein the aqueous solution comprises two or more transition metal ions and a chelating agent. Here, the two or more transition metals may be two or more metals selected from V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru.
[0105] Furthermore, in the former step, the transition metal and the chelating agent can be added to the aqueous solution in any order. In addition, the latter step can be a step of mixing the aqueous solution containing the transition metal and the chelating agent with an alkaline aqueous solution, or a step of adding a pH-raising agent to the aqueous solution containing the transition metal and the chelating agent.
[0106] In addition, the method for producing LDH of the present embodiment may further include a step of increasing the pH value of the alkaline aqueous solution. Specifically, this step may be a step of gradually increasing the pH value of the alkaline aqueous solution.
[0107] For example, the step may include a step of gradually mixing an aqueous alkali solution into an aqueous solution containing a transition metal and a chelating agent, a step of gradually dissolving a pH-increasing agent added to such an aqueous solution into the aqueous solution, and the like.
[0108] Furthermore, the method for producing LDH of the present embodiment can make the aqueous solution containing two or more transition metal ions and a chelating agent alkaline at room temperature, or can increase the pH of the alkaline aqueous solution containing two or more transition metal ions and a chelating agent at room temperature.
[0109] Thus, the method for producing LDH according to the present embodiment can suppress the chelating agent coordinated to the transition metal ion from being decomposed by heat by performing the synthesis process of LDH at room temperature.
[0110] As described above, the method for producing LDH according to the present embodiment can obtain LDH that exhibits higher catalytic activity than conventional LDH in the anode reaction of water electrolysis.
[0111] For example, the method for producing LDH of the present embodiment, by including a chelating agent, can obtain LDH showing high catalytic activity in the anode reaction of water electrolysis compared to the case where the chelating agent is not included. Specifically, it is known that when LDH to which a chelating agent is added is used as a catalyst for a water electrolysis unit, the oxygen production current of the anode reaction of water electrolysis increases compared to the case where the chelating agent is not added. The details are described in the evaluation of the embodiment.
[0112] (Second embodiment)
[0113] The LDH and the method for producing LDH of the present embodiment are the same as the LDH and the method for producing LDH of the first embodiment, except that the two or more transition metals include any one of Ni and Fe.
[0114] It is known that among transition metals, nickel (Ni) and iron (Fe) have particularly high catalytic activity for the anode reaction of water electrolysis. Therefore, the LDH of the present embodiment can show high catalytic activity in the anode reaction of water electrolysis by containing any one of Ni and Fe, compared with the case of selecting other transition metals. In addition, since Ni and Fe are abundantly present elements, the LDH of the present embodiment and the method for manufacturing LDH can reduce material costs by containing any one of Ni and Fe, compared with the case of selecting other transition metals.
[0115] Here, in the LDH of the present embodiment, the two or more transition metals may be composed of Ni and Fe, and the ratio of the amount of Fe to the total amount of Ni and Fe may be 0.25 to 0.5.
[0116] It is known that when the transition metal in LDH is composed of Ni and Fe, when the above ratio is 0.25 or more and 0.5 or less, LDH has particularly high catalytic activity for the anode reaction of water electrolysis. The details are described in the evaluation of the examples.
[0117] Therefore, the LDH of the present embodiment contains Ni and Fe in a ratio within a range of 0.25 to 0.5, and thus can exhibit high catalytic activity in the anode reaction of water electrolysis compared to the case where the ratio is outside the above range.
[0118] The LDH and the method for producing the LDH of the present embodiment may be the same as those of the first embodiment except for the above-mentioned features.
[0119] (Third embodiment)
[0120] The LDH and the method for producing LDH of the present embodiment are the same as the LDH and the method for producing LDH of the first embodiment, except that the chelating agent includes acetylacetone (ACAC) and a citrate such as trisodium citrate or magnesium citrate.
[0121] Here, in the LDH of the present embodiment, the chelating agent may be ACAC, and the absorbance at 300 nm when the optical path length is 10 mm obtained by ultraviolet visible absorbance measurement (UV-vis) may be 0.75 or more and 1.0 or less.
[0122] When the coordination amount of the chelating agent is such that the absorbance at 300 nm obtained by UV-vis absorbance measurement is 0.75 or more and 1.0 or less, the aggregation of LDH nanoparticles can be inhibited. In addition, when LDH is used as a catalyst material, the inhibitory effect of the chelating agent can also be obtained.
[0123] In addition, in the method for producing LDH of the present embodiment, the solubility of the complex of the transition metal and the chelating agent in water may be 2 g / L or more.
[0124] Therefore, the method for producing LDH of the present embodiment can appropriately ensure the concentration of transition metal ions in the aqueous solution required for LDH synthesis by reaction between transition metal ions in the aqueous solution, as compared with the case where the solubility of the complex of the transition metal and the chelating agent in water is greater than 2 g / L.
[0125] It is generally known that the solubility of the complex of transition metal and ACAC and the solubility of the complex of transition metal and citrate are 2 g / L or more. Therefore, as the chelating agent in the method for producing LDH of the present embodiment, either ACAC or citrate can be used.
[0126] The LDH and the method for producing the LDH of the present embodiment may be the same as those of the first embodiment or the second embodiment except for the above-mentioned features.
[0127] (Fourth embodiment)
[0128] The method for producing LDH of the present embodiment is the same as the method for producing LDH of the first embodiment, except that the chelating agent is added at a concentration of 1 / 2.5 or less of the transition metal ion concentration.
[0129] According to the above, the manufacture method of LDH of the present embodiment, by adding a chelating agent at a concentration below 1 / 2.5 of the transition metal ion concentration, compared with the situation of adding the addition amount of the chelating agent at a concentration greater than 1 / 2.5 of the transition metal ion concentration, can obtain LDH showing high catalytic activity in the anode reaction of water electrolysis. For example, it will be described in the evaluation of the embodiment, and it is known that the nanoparticleization of LDH is difficult when a chelating agent is added at a concentration of 1 / 2 of the transition metal ion concentration.
[0130] The LDH and the method for producing the LDH of the present embodiment may be the same as any one of the first to third embodiments except for the above-mentioned features.
[0131] (Fifth embodiment)
[0132] Figure 6 This is a diagram showing an example of a water electrolysis unit according to the fifth embodiment.
[0133] exist Figure 6 In the example shown, the water electrolysis unit 200 includes an electrolyte 31 , a positive electrode AN, and a negative electrode CA.
[0134] The electrolyte 31 may be, for example, an electrolyte membrane having ion conductivity. The electrolyte membrane may have any structure as long as it has ion conductivity. For example, a Sustanion (trademark) film having anion exchange properties may be used as the electrolyte membrane.
[0135] The positive electrode AN comprises a catalyst layer 30 such as Figure 6As shown by the double-dashed line, the porous and conductive gas diffusion layer 33 can be provided on the catalyst layer 30. Here, the catalyst layer 30 is provided on one main surface of the electrolyte membrane. The catalyst of the catalyst layer 30 is a catalyst for a water electrolysis unit including the LDH of the first embodiment.
[0136] The negative electrode CA includes a catalyst layer 32 such as Figure 6 As shown by the double-dashed line of , the porous and conductive gas diffusion layer 34 can be provided on the catalyst layer 32. Here, the catalyst layer 32 is provided on the other main surface of the electrolyte membrane. The catalyst layer 32 can contain, for example, platinum (Pt) as a catalyst metal, but is not limited thereto. For example, the catalyst of the catalyst layer 32 can also be composed of the LDH of the first embodiment in the same manner as the catalyst layer 30.
[0137] According to the above, the water electrolysis unit 200 of the present embodiment can show a higher catalytic activity than before in the water electrolysis unit anode reaction of water electrolysis. Even in the state of the water electrolysis unit, the chelating agent remains in the catalyst to suppress the aggregation of the catalyst, and the energy conversion efficiency of water electrolysis is improved due to the increase in catalytic active points.
[0138] The water electrolysis unit 200 of this embodiment may be similar to any one of the first to fourth embodiments except for the above-mentioned features.
[0139] (Sixth embodiment)
[0140] Figure 7 This is a diagram showing an example of a water electrolysis device according to a sixth embodiment.
[0141] exist Figure 7 In the illustrated example, the water electrolysis device 300 includes a water electrolysis unit 200 and a voltage applicator 40. Here, the water electrolysis unit 200 is the same as the water electrolysis unit 200 of the fifth embodiment, and thus description thereof is omitted.
[0142] The voltage applicator 40 is a device that applies a voltage to the positive electrode AN and the negative electrode CA of the water electrolysis unit 200 .
[0143] Specifically, the high potential of the voltage applicator 40 is applied to the positive electrode AN, and the low potential of the voltage applicator 40 is applied to the negative electrode CA. The voltage applicator 40 may be of any configuration as long as it can apply a voltage between the positive electrode AN and the negative electrode CA. For example, the voltage applicator 40 may be a device for adjusting the voltage applied between the positive electrode AN and the negative electrode CA. Specifically, the voltage applicator 40 has a DC / DC converter when connected to a DC power source such as a battery, a solar cell, or a fuel cell, and has an AC / DC converter when connected to an AC power source such as an industrial power source. In addition, the voltage applicator 40 is an electric power source that adjusts the voltage applied between the positive electrode AN and the negative electrode CA and the current flowing between the positive electrode AN and the negative electrode CA in such a way that the power supplied to the water electrolysis device 300 becomes a specified set value.
[0144] According to the above, the water electrolysis device 300 of the present embodiment can show a higher catalytic activity than before in the anode reaction of water electrolysis. Even in the state of the water electrolysis device, the chelating agent remains in the catalyst to suppress the aggregation of the catalyst, and the energy conversion efficiency of water electrolysis is improved due to the increase in catalytic active points.
[0145] The water electrolysis device 300 of this embodiment may be similar to any one of the first to fifth embodiments except for the above-mentioned features.
[0146] (Example)
[0147] In the modulation of LDH in this embodiment, the samples of Examples 1 to 9 and Comparative Example 1 are prepared by changing the molar ratio Q of ACAC to (Ni+Fe) (i.e., molar ratio Q=ACAC / (Ni+Fe)) and the molar ratio R of Fe to (Ni+Fe) (i.e., molar ratio R=Fe / (Ni+Fe)) as follows.
[0148] (Example 1)
[0149] Nickel chloride hexahydrate (427.8 mg, purchased from Fujifilm Wako Pure Chemical Industries, Ltd.) and ferric chloride hexahydrate (243.3 mg, purchased from Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in a mixed solvent (volume ratio of 2:3) of water (671 μl) and ethanol (1007 μl, purchased from Fujifilm Wako Pure Chemical Industries, Ltd.) to prepare a solution. In the solution, the total concentration of the two metal ions was 1.0 M, and the ratio of the amount of Fe to the total amount of Ni and Fe (i.e., molar ratio R) was 0.33. ACAC (92 μl, purchased from Sigma-Aldrich) was added as a chelating agent to the solution. In the solution, the molar ratio of ACAC to the total amount of Ni and Fe ions (i.e., molar ratio Q) was 1 / 3. The solution was stirred for 30 minutes. Then, propylene oxide (hereinafter referred to as "POX", 915 μl, purchased from Fujifilm Wako Pure Chemical Industries, Ltd.) was added as a pH-raising agent. The molar ratio of POX in the solution to chloride ions was 2. The solution was stirred for 1 minute. At this time, the pH of the solution gradually increased because POX slowly captured hydrogen ions in the solution. After the solution was left to stand for about 3 days, the LDH of the target sample was recovered.
[0150] It should be noted that the above LDH modulation method is only an example and is not limited to this example.
[0151] (Example 2)
[0152] LDH was produced by the same procedure as in Example 1 except that the amount of ACAC added was 138 μl, that is, the amount of ACAC added was set to half the total amount of Ni and Fe.
[0153] (Example 3)
[0154] LDH was produced by the same procedure as in Example 1 except that the amount of ACAC added was 110 μl, that is, the amount of ACAC added was 1 / 2.5 of the total amount of Ni and Fe.
[0155] (Example 4)
[0156] LDH was produced by the same procedure as in Example 1 except that the amount of ACAC added was 79 μl, that is, the amount of ACAC added was 1 / 3.5 of the total amount of Ni and Fe.
[0157] (Example 5)
[0158] LDH was produced by the same procedure as in Example 1 except that the amount of ACAC added was 74 μl, that is, the amount of ACAC added was 1 / 3.75 of the total amount of Ni and Fe.
[0159] (Example 6)
[0160] LDH was prepared in the same manner as in Example 1 except that the added amounts of nickel chloride hexahydrate, ferric chloride hexahydrate and POX were 534.8 mg, 121.7 mg and 850 μl, respectively, that is, the ratio of the amount of Fe to the total amount of Ni and Fe was set to 0.17.
[0161] (Example 7)
[0162] LDH was prepared in the same manner as in Example 1 except that the added amounts of nickel chloride hexahydrate, ferric chloride hexahydrate and POX were 481.3 mg, 182.5 mg and 882 μl, respectively, that is, the ratio of the amount of Fe to the total amount of Ni and Fe was set to 0.25.
[0163] (Example 8)
[0164] LDH was prepared in the same manner as in Example 1 except that the added amounts of nickel chloride hexahydrate, ferric chloride hexahydrate and POX were 320.9 mg, 365.0 mg and 980 μl, respectively, that is, the ratio of the amount of Fe to the total amount of Ni and Fe was set to 0.50.
[0165] (Example 9)
[0166] LDH was prepared in the same manner as in Example 1 except that the added amounts of nickel chloride hexahydrate, ferric chloride hexahydrate and POX were 213.9 mg, 486.6 mg and 1046 μl, respectively, that is, the ratio of the amount of Fe to the total amount of Ni and Fe was set to 0.67.
[0167] (Comparative Example 1)
[0168] LDH was prepared by the same procedure as in Example 1 except that ACAC was not added.
[0169] Table 1 shows a list of parameters changed in Examples 1 to 9 and Comparative Example 1 described above.
[0170] Table 1
[0171]
[0172] (Example 10)
[0173] A membrane-electrode assembly (MEA) in which the sample obtained in Example 1 was mounted on a catalyst layer was prepared as follows.
[0174] The sample of Example 1 (LDH) and Ketjen Black (KB) were dispersed in a mixed solvent of water and ethanol (mass ratio: 7:9) at a mass ratio of 2:1.
[0175] Next, 20 wt % of Nafion (registered trademark) dispersion was added to the solution as a binder to prepare a mixed dispersion of LDH / KB / Nafion (registered trademark) in which the mass of Nafion (registered trademark) was 0.3 times the total mass of LDH and KB.
[0176] Then, anode catalyst ink was prepared by performing a micronization process using a ball mill (ball diameter: Φ1.3 mm, rotation speed: 400 rpm, treatment time: 80 minutes) and an ultrasonic homogenizer (treatment time: 30 minutes).
[0177] Next, a cathode catalyst ink was prepared by the same procedure as the anode catalyst ink except that the catalyst and the carrier were Pt and KB (mass ratio was 1:1).
[0178] Next, the anode catalyst ink and the cathode catalyst ink were sprayed onto carbon paper, respectively, to produce anode and cathode gas diffusion electrodes (GDE: Gas Diffusion Electrode).
[0179] Next, a sandwich structure MEA was fabricated by sandwiching Sustanion (trademark) as an anion exchange membrane between an anode gas diffusion electrode and a cathode gas diffusion electrode. Then, an electrolysis experiment was conducted using a water electrolysis device equipped with the MEA. The details of the electrolysis experiment are described in Evaluation 7.
[0180] Furthermore, the water electrolysis device is appropriately provided with equipment and components required for conducting electrolysis experiments. For example, in addition to the above-mentioned MEA, a gasket for leak prevention, a partition with a serpentine flow path, a power supply plate, an insulating plate, and a fixing fixture with a supply port and a discharge port for the solution are provided around the MEA.
[0181] The above-mentioned structure of MEA and the structure of the water electrolysis device are only examples, and are not limited to these examples.
[0182] [Evaluation 1: Evaluation by observation over time in solution]
[0183] In Example 1, the solution gelled within 1 hour from the addition of POX. It is believed that this is because, as the pH value of the solution increases, the hydroxide precipitate of Fe is generated and grows. Moreover, after about 36 hours from the addition of POX, the solution solubilized again. It is believed that this is because, when the pH value of the solution increases to the area where Ni precipitates, the LDH formation reaction occurs between the Fe-ACAC complex and Ni, and thus the dissolution reaction of Fe from the hydroxide precipitate of Fe caused by ACAC continues. That is, it is believed that the occurrence of such resolubilization shows that the synthesis of LDH nanoparticles is carried out while suppressing the aggregation of LDH nanoparticles.
[0184] In Examples 3, 4, 6, 7, 8, and 9, there were some differences in reaction rates, but the same phenomenon as in Example 1 was confirmed.
[0185] On the other hand, in Examples 2 and 5 and Comparative Example 1, although the solution was gelled, it did not resolubilize.
[0186] The results of Evaluation 1 are summarized in Table 2 below.
[0187] Table 2
[0188] Gelation Resolubilization Example 1 ○ ○ Example 2 ○ × Example 3 ○ ○ Example 4 ○ ○ Example 5 ○ × Example 6 ○ ○ Example 7 ○ ○ Example 8 ○ ○ Example 9 ○ ○ Comparative Example 1 ○ ×
[0189] [Evaluation 2: Observation and evaluation of the dispersion state of the sample]
[0190] The samples obtained in Examples 1 to 9 and Comparative Example 1 were dispersed in a mixed solvent of water and ethanol (the volume ratio of water to ethanol was 1:4), and the dispersion states of these samples were observed.
[0191] The samples obtained in Examples 1, 3, 4, 6, 7, 8 and 9 were dispersed in the mixed solvent without generating precipitation of solid matter, thereby forming an orange transparent colloidal solution.
[0192] In contrast, the samples obtained in Examples 2, 5 and Comparative Example 1 were difficult to recover in a gelled state, but they were forcibly dried to recover and dispersed in the same solvent. For the sample obtained in Comparative Example 1, an orange but turbid liquid was formed, and a certain amount of particles were precipitated in the lower part of the container. Thus, regarding the sample obtained in Comparative Example 1, since a well-dispersed colloidal solution was not formed, it can be said that its particle size is more than several hundred nm. On the other hand, regarding the samples obtained in Examples 2 and 5, no precipitate was confirmed as in the case of the sample obtained in Comparative Example 1. It is inferred that the particle size of the samples obtained in Examples 2 and 5 did not increase as much as the particle size of the sample obtained in Comparative Example 1.
[0193] From the above, it is considered that the samples obtained in Examples 1, 3, 4, 6, 7, 8, and 9 have a smaller average particle size than the sample obtained in Comparative Example 1.
[0194] [Evaluation 3: Material identification evaluation]
[0195] The crystal phase of the sample was measured using an X-ray diffraction device (XRD; PANalytical, X'Pert PRO) under the measurement conditions of voltage 45 kV, current 40 mA, and measurement range 5 to 70° to obtain each XRD spectrum.
[0196] As a result, in all of the samples obtained in Examples 1, 3, 4, 6, 7, 8, and 9, and Comparative Example 1, a peak corresponding to LDH was confirmed.
[0197] Again, as an example, Figure 8 This is a diagram showing an example of an XRD spectrum of a sample obtained in Example 1.
[0198] From the above, it was found that the samples obtained in Examples 1, 3, 4, 6, 7, 8 and 9 and Comparative Example 1 were LDH.
[0199] When the results of Evaluation 1 and Evaluation 2 are considered together with the results of Evaluation 3, it is believed that by setting the added concentration of the chelating agent to an appropriate amount, LDH nanoparticles can be appropriately synthesized while suppressing aggregation of LDH nanoparticles, and the solution is resolubilized during the synthesis process.
[0200] [Evaluation 4: Particle size evaluation using SAXS]
[0201] The average particle size of the sample obtained in Example 1 was evaluated by small-angle X-ray scattering (SAXS; SmartLab, Rigaku).
[0202] Fig. 9 This is a diagram showing an example of the particle size distribution of the sample obtained in Example 1 (particle size distribution reflecting the particle sizes of primary particles and secondary particles). Fig. 9 The horizontal axis is taken as particle size. Fig. 9 The vertical axis is taken as the number of particles (arbitrary units).
[0203] Here, the so-called "average particle size" refers to: in the particle size distribution obtained by small angle X-ray scattering (SAXS), Fig. 9 When the relationship between the particle size and the number of particles is expressed by a two-dimensional distribution graph as shown, the value is obtained by dividing the area of the two-dimensional distribution graph (that is, the product of the particle size and the number of particles corresponding to the particle size) by the total number of particles.
[0204] Therefore, by Fig. 9The particle size distribution of the sample obtained in Example 1 was evaluated, and the average particle size was 7.2 nm.
[0205] In addition, the average particle diameters of the samples obtained in Examples 3, 4, 7, and 8 in the same manner were 5.6 nm, 1.3 nm, 6.8 nm, and 6.0 nm.
[0206] The above results are consistent with the findings of the inventors of the present invention that by setting the added concentration of the chelating agent to an appropriate amount, LDH nanoparticles can be appropriately synthesized while suppressing the aggregation of LDH nanoparticles.
[0207] [Evaluation 5: Evaluation using ultraviolet visible absorbance measurement (UV-vis)]
[0208] For the samples obtained in Examples 1, 3 and 4 and Comparative Example 1, in order to confirm whether ACAC exists and, if ACAC exists, to evaluate the amount of ACAC, an ultraviolet-visible absorption spectra of the samples obtained in Examples 1, 3 and 4 and Comparative Example 1 were confirmed using an ultraviolet-visible absorbance measuring device (UV-vis, UV-3600Plus, manufactured by Shimadzu Corporation) under the condition of an optical path length of 10 mm.
[0209] As a result, for the samples obtained in Examples 1, 3, and 4, an absorption peak was confirmed near 300 nm. Figure 3 As shown in (b), the molecules formed by chelation with ACAC have an absorption peak at a wavelength of about 300nm in the UV-visible absorption spectrum based on UV-vis. Therefore, this peak is the absorption peak of ACAC coordinated with Fe and Ni. In addition, for the samples obtained in Examples 1, 3 and 4, the absorbance of the peak near 300nm is 0.98, 1.00, and 0.76, respectively, which is a result that the absorbance increases with the increase of the ACAC addition concentration in Table 1.
[0210] On the other hand, in the sample obtained in Comparative Example 1, no absorption peak was confirmed near 300 nm.
[0211] In addition, the ultraviolet-visible absorption spectra of the samples obtained in Examples 7 and 8 were also confirmed by UV-vis, and similarly, absorption peaks were confirmed near 300 nm. Thus, the presence of ACAC coordinated with Fe and Ni was confirmed in these samples as well.
[0212] [Evaluation 6: Catalytic activity evaluation]
[0213] The samples obtained in Examples 1, 3, 4, 6, 7, 8 and 9 and Comparative Example 1 were evaluated as catalysts for a water electrolysis unit in the following manner.
[0214] In this evaluation, a potentiostat (VersaSTAT4, Princeton Applied Research) and a rotating electrode (RDE; Pine Research, electrode model AFE3T050GC) were used to measure the current derived from the anode reaction (oxygen generation reaction) of the water electrolysis unit under the following measurement conditions.
[0215] Solution: 1M KOH solution
[0216] Potential: 1.1V~1.65V (vs. reversible hydrogen electrode (RHE))
[0217] Potential sweep speed: 10mV / sec
[0218] Electrode rotation speed: 1500rpm
[0219] Table 3 below shows an example of the relationship between the oxygen generation current (current density) at a potential of 1.65 V (vs. RHE) and the molar ratio R in LDH (that is, the molar ratio of Fe to (Ni+Fe)).
[0220] Table 3
[0221] Molar Ratio Current density Example 1 0.33 200 Example 6 0.17 127 Example 7 0.25 200 Example 8 0.50 221 Example 9 0.67 159
[0222] As shown in Table 3, when the samples obtained in Examples 1, 6, 7, 8 and 9 were used as catalysts for water electrolysis units, when the molar ratio R was 0.25 or more and 0.5 or less, the catalytic activity for the anode reaction of water electrolysis was particularly high.
[0223] Table 4 below shows an example of the relationship between the oxygen generation current (current density) at a potential of 1.65 V (vs. RHE) and the molar ratio Q (that is, the molar ratio of ACAC to (Ni+Fe)).
[0224] Table 4
[0225] Molar Ratio Q Current density Example 1 1 / 3 200 Example 3 1 / 2.5 190 Example 4 1 / 3.5 195 Comparative Example 1 0 160
[0226] As shown in Table 4, by adopting an appropriate molar ratio Q, the samples that were resolubilized during the synthesis of LDH nanoparticles (Examples 1, 3 and 4) had a current density that was about 1.25 times higher than that of the sample that did not add ACAC and was not resolubilized (Comparative Example 1).
[0227] When the above evaluations 1 to 6 are comprehensively considered, the upper limit of the appropriate range of the molar ratio Q in the solution (i.e., the molar ratio of ACAC to (Ni+Fe)) is considered to be about 1 / 2.5. In addition, the lower limit of the appropriate range of the molar ratio Q is considered to be about 1 / 3.5.
[0228] [Evaluation 7: Performance evaluation using a water electrolysis device]
[0229] Hereinafter, the procedure and results of an electrolysis experiment performed using the water electrolysis apparatus of Example 10 will be described.
[0230] The alkaline aqueous solution was supplied from the lower part of the fixing jig of the water electrolysis device and discharged from the upper part, so that the alkaline aqueous solution was circulated in the system of the water electrolysis device, and the system was made into an alkaline atmosphere. In addition, at this time, whether a uniform pressure was applied to the electrode part of the MEA and whether there was leakage of the circulating solution were confirmed using pressure-sensitive paper, but there were no problems.
[0231] In this electrolysis test, the characteristics of the water electrolysis unit were evaluated by measuring the cell voltage during application using a constant current electrolysis step method in which the applied current was changed at regular intervals. Furthermore, as alkaline aqueous solutions, 1M KOHaq (normal temperature), 1M KOHaq (40°C), 1M KOHaq (60°C), and 1M KOHaq (80°C) were circulated in the system of the water electrolysis device in this order, thereby conducting electrolysis tests of the water electrolysis device in sequence.
[0232] The results of the above electrolysis tests show that, for example, in the case of an alkaline aqueous solution of 1 M KOHaq (80°C), at a current density of 1 A / cm 2 When the voltage of the water electrolysis unit is 1.59 V, it is equivalent to a high energy conversion efficiency (74.7%) comparable to 75% if converted in terms of energy conversion efficiency.
[0233] [Evaluation 8: Evaluation by thermal desorption-gas chromatography-mass spectrometry (TD-GC / MS)]
[0234] For the catalyst mounted on the water electrolysis device in Example 10, in order to evaluate whether ACAC exists, a thermal desorption-gas chromatography-mass spectrometry analyzer (TD-GC / MS, Turbo Matrix ATD / Clarus SQ 8T / Clarus680, manufactured by PerkinElmer) was used to confirm the TD-GC / MS spectrum of the catalyst used in Example 10. As a comparative sample, a commercially available ACAC reagent was used. The column heating conditions were: maintain at 35°C for 5 minutes → increase the temperature to 100°C at 10 degrees per minute → increase the temperature to 290°C at 20°C per minute → maintain at 290°C for 19 minutes, and the column heating conditions were as follows.
[0235] As a result, a signal was detected at the same retention time as the ACAC reagent for the catalyst used in Example 10. In addition, the mass spectrum of the signal was the same as the mass spectrum of the ACAC reagent. From the above, it can be seen that ACAC also exists in the catalyst mounted on the water electrolysis device in Example 10.
[0236] Furthermore, it will be apparent to those skilled in the art that many modifications and other embodiments of the present disclosure can be made clear from the above description. Therefore, the above description should be interpreted only as an example, and the best mode for implementing the present disclosure is provided for the purpose of teaching those skilled in the art. The operating conditions, composition, structure and / or function can be substantially changed without departing from the spirit of the present disclosure.
[0237] Industrial Applicability
[0238] One embodiment of the present disclosure can be utilized for LDH which can exhibit higher catalytic activity than ever before in the anode reaction of water electrolysis.
[0239] Description of Reference Numerals
[0240] 10: Main layer
[0241] 20: Object Layer
[0242] 30: Catalyst layer
[0243] 31: Electrolytes
[0244] 32: Catalyst layer
[0245] 33: Gas Diffusion Layer
[0246] 34: Gas Diffusion Layer
[0247] 40: Voltage applicator
[0248] 50: LDH nanoparticles
[0249] 200: Water electrolysis unit
[0250] 300: Water electrolysis device
[0251] AN: positive electrode
[0252] CA: negative electrode
Claims
1. A layered double hydroxide comprising two or more transition metals and a chelating agent, wherein the average particle size is 10 nm or less, wherein the two or more transition metals are composed of Ni and Fe, and the ratio of the amount of Fe to the total amount of Ni and Fe is 0.25 or more and 0.5 or less.
2. The layered double hydroxide according to claim 1, The chelating agent includes any one of acetylacetone and citrate.
3. The layered double hydroxide according to claim 1 or 2, The chelating agent is acetylacetone, The absorbance at 300 nm when the optical path length is 10 mm obtained by ultraviolet visible absorbance measurement (UV-vis) is 0.75 or more and 1.0 or less.
4. The layered double hydroxide according to claim 1 or 2, The average particle size obtained by small-angle X-ray scattering (SAXS) was 10 nm or less.
5. The layered double hydroxide according to claim 1 or 2, Use [M 2+ 1-x M 3+ x (OH)2][yA n- ·mH2O] composition formula, and, The chelating agent coordinates with the two or more transition metals, In the composition formula, M 2+ is a divalent transition metal, M 3+ A is a trivalent transition metal. n- is the interlayer anion, m is an appropriate rational number, n is an integer, x is a rational number not exceeding 1, and y is a number equivalent to the amount required for charge balance. 6 . A catalyst for a water electrolysis unit, comprising the layered double hydroxide according to claim 1 .
7. A water electrolysis unit comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the catalyst according to claim 6.
8. A water electrolysis unit comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises the catalyst according to claim 6. 9 . A water electrolysis device comprising the water electrolysis unit according to claim 7 or 8 , and a voltage applicator for applying a voltage to the positive electrode and the negative electrode.
10. A method for producing the layered double hydroxide according to any one of claims 1 to 5, comprising the steps of adding a chelating agent to prepare an aqueous solution and making the aqueous solution alkaline at room temperature, the aqueous solution containing two or more transition metal ions and the chelating agent.
11. The method for producing a layered double hydroxide according to claim 10, The method further comprises the step of increasing the pH value of the alkaline aqueous solution.
12. The method for producing a layered double hydroxide according to claim 11, The pH value of the alkaline aqueous solution is increased at room temperature.
13. The method for producing a layered double hydroxide according to any one of claims 10 to 12, The solubility of the complex of the transition metal and the chelating agent in water is 2 g / L or more.
14. The method for producing a layered double hydroxide according to any one of claims 10 to 12, The chelating agent includes any one of acetylacetone and citrate.
15. The method for producing a layered double hydroxide according to any one of claims 10 to 12, The chelating agent is added at a concentration of 1 / 2.5 or less of the transition metal ion concentration.
Citation Information
Patent Citations
Preparation method for high activity NiFe-LDHs catalyst
CN108940329A
Heterostructures for ultra-active hydrogen evolution electrocatalysis
US20160017507A1